Hydroxylamine-O-sulfonamide is a versatile lead compound for the development of carbonic anhydrase inhibitors1. Issue 57 (21st July 2015) - Di Fiore, Anna; Vergara, Alessandro; Caterino, Marco; Alterio, Vincenzo; Monti, Simona M.; Ombouma, Joanna; Dumy, Pascal; Vullo, Daniela; Supuran, Claudiu T.; Winum, Jean-Yves; De Simone, Giuseppina
<x xml:space="preserve">Abstract</x> Hydroxylamine-O-sulfonamide has been investigated as CA inhibitor by means of kinetic and structural studies clarifying its mechanism of action.